Release Our River, Let the Salmon Swim: Skokomish Efforts to Restore Their River - Stoffle, Richard (Frontiers in Conservation Science, 2022)
The Skokomish Indian people have successfully argued for the restoration of the North Fork of the Skokomish River on the Olympic Peninsula, USA. These people have adapted to and culturally incorporated this river since time immemorial, which is for well over 14,000 years. The tribe argued in a U.S. Federal court, helped by three cultural anthropologists, for the release of river water from the two Cushman dams managed by Tacoma Water and Power (TWP). The tribe insisted that the cultural landscape produced by the traditional flow of the river still exist despite damage from the dams. They argued that returning river water could restore the salmon natural habitat and the people could have access to their spiritual locations. In 2009 a settlement between TWP and the Skokomish Indian Nation resulted in a 2010 amendment to the Federal Energy Regulatory Commission licensing agreement for the dams. This resulted in reassertion of tribal sovereignty, including restoration of channel maintaining flows and salmon populations. The case contributes to the discussion of the Protected Landscape Approach, Category V of the International Union for Conservation of Nature, World Commission on Protected Areas.